EAST steady-state long pulse H-mode with core-edge integration for CFETR. (1st July 2022) - Gong, X.Z.; Garofalo, A.M.; Huang, J.; Qian, J.P.; Ekedah, A.; Maingi, R.; holcomb, C.T.; Liu, F.K.; Zhao, Y.P.; Xiao, B.J.; Hu, J.S.; Hu, C.D.; et al.
Abstract: A recent EAST experiment has successfully demonstrated long pulse steady-state high plasma performance scenario and core-edge integration since the last IAEA in 2018. A discharge with a duration over 60 s with β P ∼ 2.0, β N ∼ 1.6, H98y2 ∼ 1.3 and an internal transport barrier on the electron temperature channel is obtained with multi-RF power heating and current drive. A higher β N ( β N ∼ 1.8, β p ∼ 2.0, H98y2 ∼ 1.3, n e / n GW ∼ 0.75) with a duration of 20 s is achieved by using the modulated neutral beam and multi-RF power, where several normalized parameters are close or even higher than the phase III 1 GW scenario of CFETR steady-state. High-Z impurity accumulation in the plasma core is well controlled in a low level by using the on-axis ECH. Modeling shows that the strong diffusion of TEM turbulence in the central region prevents tungsten impurity from accumulating. More recently, EAST has demonstrated compatible core-edge integration discharges in the high β p scenario: high confinement H98y2 > 1.2 with high β P ∼ 2.5/ β N ∼ 2.0 and f bs ∼ 50% is sustained with reduced divertor heat flux at high density n e / n GW ∼ 0.7 and moderate q 95 ∼ 6.7. By combining active impurity seeding through radiative divertor feedback control and strike point splitting induced by resonant perturbation coil, the peak heat flux is reduced by 20–30% on the ITER-like tungsten divertor, here a mixture of 50% neon and 50% D2 is applied.